ANALISIS VARIABEL MAKROEKONOMI TERHADAP PENERIMAAN PPN DAN PPNBM DI INDONESIA: STUDI PADA PDB, INFLASI, DAN KONSUMSI RUMAH TANGGA - Pangka, Sirilus Alfredo; Budianto, Risanda Alirastra (Politeknik Negeri Ambon, 2025)
Introduction: The purpose of this research is to analyze the impact of macroeconomic factors (GDP, Inflation, Household Consumption) on VAT and luxury tax revenues in Indonesia. Methods: The research method uses a quantitative approach with secondary data from 2014–2023 from BPS, the Ministry of Finance, and Bank Indonesia. The analysis tool in the form of multiple linear regression in EViews 12.Results: The classical assumption test (normality, autocorrelation, multicollinearity, heteroscedasticity) shows satisfactory results.The regression results revealed: GDP has a significant positive effect (significance 0.0005), Inflation is not significant (significance 0.5076), Household Consumption has a significant positive effect (significance 0.0000), and the model is significant simultaneously (F-statistic 160.77). The coefficient of determination (Adjusted R²) is 95.6%. This research is expected to serve as the basis for fiscal policy to increase tax revenue through strengthening economic growth and public purchasing power, as well as to encourage further research with tax policy variables and long-term dynamic analysis. Keywords: GDP, Household Consumption, Inflation, Multiple Linear Regression, VAT and LGST.